Mobile based for inventory system (MBIS) - Che Normadiaa, Ibrahim (2018)
The title of this project is Mobile Based for Inventory System (MBIS). This system plays an important role to help seller especially stockist to manage their inventory, inbound and outbound of the product and track the availability of product. Before this, most of the seller recorded their inventory just in log book only. With this way, the probability loses of data may happen and directly this matter can effected their inventory. So, the objectives of developing this system is to analyse the problem of current system by produce Mobile Based for Inventory System, to design and develop prototype system for Mobile Based for Inventory System using Google Excel as a system database management and to test the prototype of Mobile Based for Inventory System. MBIS is developed by using Android Studio with Java language. In addition, cloud computing will be used to support a system database management and make a system more friendly. The methodology used in developing this system is Agile Methodology that consist of five phases which are planning, requirement, design, building and testing that allows the system to be developed quickly and easily implement the changes even during the development of the system. Before deliver the system, full testing toward the system will be performed to ensure the system has meet the user requirements and objectives.